Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00253-014-5802-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol supplementation of the growth medium enhances in situ detoxification of furfural by Clostridium beijerinckii during butanol fermentation

Abstract: Lignocellulose-derived microbial inhibitors such as furfural and 5-hydroxymethyl furfural adversely affect fermentation of lignocellulosic biomass hydrolysates to fuels and chemicals due to their toxicity on fermenting microbes. To harness the potential of lignocellulose as a cheap source of fermentable sugars, in situ detoxification of furfural and other lignocellulose-derived microbial inhibitors is essential. To enhance in situ detoxification and tolerance of furfural by Clostridium beijerinckii NCIMB 8052 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 40 publications
1
58
0
Order By: Relevance
“…Similar effects might occur to Clostridium species during ABE fermentation. The results of some studies (Ezeji et al 2007a;Qureshi et al 2010a;Ujor et al 2014;Zhang and Ezeji 2013;Zheng et al 2009b) also supported the similarity of toxicity effects between ABE and ethanol fermentation. Overall, the presence of these toxic compounds inhibited microbial cell growth and affected inhibition of glycolytic and fermentative enzymes, which are essential to central metabolic pathways.…”
Section: Metabolic Effects Of Inhibitorssupporting
confidence: 69%
See 3 more Smart Citations
“…Similar effects might occur to Clostridium species during ABE fermentation. The results of some studies (Ezeji et al 2007a;Qureshi et al 2010a;Ujor et al 2014;Zhang and Ezeji 2013;Zheng et al 2009b) also supported the similarity of toxicity effects between ABE and ethanol fermentation. Overall, the presence of these toxic compounds inhibited microbial cell growth and affected inhibition of glycolytic and fermentative enzymes, which are essential to central metabolic pathways.…”
Section: Metabolic Effects Of Inhibitorssupporting
confidence: 69%
“…They found that two enzymes encoded by Cbei_3974 and Cbei_3904 and belonging to the aldo/keto reductase and short-chain dehydrogenase/reductase families, respectively, were involved in furfural detoxification and tolerance. Moreover, recent studies (Qureshi et al 2012;Ujor et al 2014) found that the increase in HMF and furfural concentrations resulted in a decline in ABE (Fig. 7).…”
Section: Effects Of Microbial Inhibitors On Abe Productionmentioning
confidence: 91%
See 2 more Smart Citations
“…Since detoxification of furfural and HMF siphons NAD(P)H, thereby disrupting cellular redox balance and hampering cofactor-dependent biosynthetic reactions, we have been evaluating different strategies to enhance the availability of cellular reductants. For example, we recently reported that supplementation of the fermentation medium with glycerol, a more reduced substrate than glucose, led to a 2.3-fold increase in the rate of detoxification of 5 g/L furfural, substrate consumption, and acetone-butanol-ethanol (ABE) production by C. beijerinckii (Ujor et al 2014). We also showed that these benefits were likely due to the ability of glycerol to increase the NADH and NADPH levels by 1.8-and 3-fold, respectively.…”
Section: Introductionmentioning
confidence: 99%